Routes to cellulosic ethanol - Buckeridge, Marcos Silveira; Goldman, Gustavo Henrique; SpringerLink (Online service). (New York Springer, 2011)
The quest for renewable energy and sustainability have led to the examinaiton of using biomass as a source of energy. Since large amounts of energy are "hidden" in carbon polymers made by plants, notably carbohydrates, the development of technologies to produce liquid fuels from carbohydrate polymers such as cellulose could significantly increase energy sustainabiligy. This book reviews general aspects of biomass utilization for bioenergy production, as well as strategies using biochemistry, molecular biology, chemistry and physics to disassemble plant cell walls. Recent discoveries of basic science under development in several laboratories are reviewed by experts who have been working intensively with aspects that will have an impact on the development of the technology of production of cellulosic ethanol -- Source other than Library of Congress.
Bioenergy -- The role of biomass in the world's energy system -- BioEnergy and the Sustainable Revolution -- Biomass gasification for ethanol production -- Plant cell walls, enzymes and metabolism -- Hemicelluloses as Recalcitrant Components for Saccharification in Wood.-Topochemistry, porosity and chemical composition affecting enzymatic hydrolysis of lignocellulosic materials -- Enzymology of plant cell wall breakdown: an update -- Enzymes in Bioenergy -- Hydrolases from microorganisms used for degradation of plant cell wall and bioenergy production -- Cellulase Engineering for Biomass Saccarification -- Genetic improvement of xylose utilization by Saccharomyces cerevisiae -- Plant cell wall genetics -- Tropical Maize: Exploiting maize genetic diversity to develop a novel annual crop for lignocellulosic biomass and sugar production -- Sugarcane breeding and selection of sugar cane with higher lignocellulosic ethanol production -- Cell Wall Genomics in the Recombinogenic Moss Physcomitrella patens.
Electronic reproduction.
Keywords: Cellulose -- Biotechnology; Biomass energy; Plant cell walls; Ethanol as fuel; Electronic books